PURCHASE ORDER AS A REPRESENTATION OF THE AGREEMENT BETWEEN THE PARTIES IN A CONTRACTUAL RELATIONSHIP OF FURNITURE SALES - Rudi Hartono; Benhard Kurniawan Pasaribu; Kamaluddin; Fatimah Asyari (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study analyzes the legal status of Purchase Orders as a manifestation of the parties' agreement in a furniture sales contractual relationship through a normative study of the principles of consensualism, freedom of contract, and legal implications in Indonesian civil law. Normatively, Article 1320 and Article 1338 of the Civil Code emphasize that the validity of an agreement is determined by the fulfillment of the elements of the parties' agreement, not merely the formal form of the document. However, in practice, there are still differences in understanding regarding the legal status of Purchase Orders that have the potential to cause disputes, especially in made-to-order transactions . This study uses a normative legal method with a statutory, conceptual, and case approach. The results of the study indicate that Purchase Orders can be qualified as binding agreements as long as they meet the legal requirements of an agreement, thus giving rise to rights and obligations as well as implications of default if violated. Therefore, it is necessary to strengthen legal construction, establish consistent jurisprudence, and standardize Purchase Order documents to provide legal certainty and protection in trade practices.